A prospective study of clinical manifestations of snake bite in government general hospital - Reddy, Yadavendra C. (International Journal of Research in Medical Sciences, 2019)
Background: Snake bite is an occupational and rural hazard because India has always been a land of exotic snakes. Although full burden of human suffering attributable to snake bite remains obscure, hundreds of thousands of people are known to be envenomed and tens of thousands are killed or maimed by snakes every year. This study is aimed at studying the clinical manifestations in snake bite at government general hospital. Methods: This Prospective Observational study was done from March 2019 to August 2019 in Government General Hospital Nalgonda. A total of 60 cases male and female admitted with snake bite were studied based on inclusion and exclusion criteria. All patients were done routine investigations, ECG was done to rule out cardiac anomalies. Patients below 12 years, pregnant women and patients with previous heart ailments were excluded from the study. The study was carried out in all patients fulfilling the inclusion and exclusion criteria. Results: A total of 60 patients 35 females and 25 males presented during the study period. Most of the patients presented with pain at the site 40(66%), Nausea 30(50%), Swelling 25(42%), Paraesthesia 25(42%), Bleeding 15(25%), Ptosis 15(25%), Sweating 10(17%), Cellulitis 10(17%) and dyspnoea 5(9%). Among the ECG manifestations- Tachycardia- 30(50%), Ischaemia 5(9%), Sinus arrythmia 2(4%), Myocardial Infarction-0. Conclusions: It was Observed from the study that the pt. had more of Haemolytic presentation than neuroparalytic presentation. Pain at the site was the most common presentation followed by nausea. Some patients developed neuroparalytic symptoms like cellulitis, and paraesthesia. Further it was observed that timely shifting to the Hospital and administration of Anti-Snake venom prevented major manifestations in the patients.